SYNTHESIS OF BINUCLEAR ZINC (II) COMPLEXES OF N2O2 DONORS CONTAINING 4-AMINOANTIPYRINE BASED SCHIFF BASE LIGAND AND THEORETICAL STUDIES - Sivalingam Lakshmanan (International Journal of Modern Agriculture, 2020)
Schiff-base polydentate ligands types of salen and salophen can form stable complexes with Zn and these metal complexes can act as a source of zinc. The ground state electronic structures of Zn(dptpp)2Cl2 complexes were investigated by DFT/B3LYP theoretical analysis using 6-311G++(d,p) and LANL2DZ basis set level. The molecular docking studies showed that complex Zn(dptpp)2Cl2 strongly binds with BCL-2 receptor. The results indicate that the metal complexes are more active as compared with the ligand. The docking score found to be -7.92kcal/mol against BCL-2 (PDB id: Bcl-xl: 2YXJ). From the present study, it can be conclude that the molecular docking studies showed that complex Ni (II) strongly binds with Bcl-2 receptor..